Expression of a Small Ubiquitin-Like Modifier Protease Increases Drought Tolerance in Wheat (Triticum aestivum L.) - le Roux, Marlon L.; Kunert, Karl J.; van der Vyver, Christell; Cullis, Christopher A.; Botha, Anna-Maria (Frontiers in Plant Science, 2019)
Post-translation modification of proteins plays a critical role in cellular signalling processes. In recent years, the SUMO (Small Ubiquitin-Like Modifier) class of molecules has emerged as an influential mechanism for target protein management. SUMO proteases play a vital role in regulating pathway flux and are therefore ideal targets for manipulating stress-responses. In the present study, the expression of an A. thaliana cysteine protease (OVERLY TOLERANT TO SALT-1, OTS1) in wheat (Triticum aestivum L.) has led to improved plant growth under water stress conditions. Transformed wheat (pUBI-OTS1) displayed enhanced growth and delayed senecence under water deficit when compared with untransformed Gamtoos-R genotype or plants carrying an empty vector. Transformed pUBI-OTS1 plants also maintained a high relative moisture content (RMC), had a higher photosynthesis rate, and also had a higher total chlorophyll content when compared to untransformed plants or plants carrying an empty vector. SUMOylation of total protein also increased in untransformed plants but not in the AtOTS1 transformed plants. Our results suggest that SUMO-proteases may influence an array of mechanisms in wheat to the advantage of the crop to be more tolerant to water stress caused by drought. This is the first report to elucidate SUMOylation effects in the hexaploid crop wheat (Triticum aestivum L.).